Pengaruh Kualitas Kehidupan Kerja, Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Pada Badan Penangulangan Bencana Daerah Kabupaten Lumajang) - Deve Yuandari; Budi Wahono; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis type of research uses explanatory research (quantitative research) through a quantitative approach. The location of the study was conducted at the Lumajang Regional Disaster Management Agency located at Jalan Hasanudin No. 4, Tompokersan, Lumajang, Rogotrunan, Jogotrunan, Kec. Lumajang, Lumajang Regency, East Java 67311, Indonesia. Data collection techniques are carried out by distributing questionnaires distributed to all employees who work at the Lumajang Regional Disaster Management Agency. The study population was 63 employees of the Lumajang Regional Disaster Management Agency. The determination of the sample in this study uses a saturated sampling technique. The saturation sampling technique is a sampling technique that makes all members of the population sampled. The results of this study indicate that the quality of work life has a positive and significant effect on employee performance, motivation doesn’t significantly influence employee performance, work discipline affects employee performance.Keyword: Employee Performance, Quality of Work Life, Motivation, Work Discipline